Workflows for microscopy image analysis and cellular phenotyping - Wollmann, Thomas; Erfle, Holger; Eils, Roland; Rohr, Karl; Gunkel, Manuel (Journal of biotechnology, 2017)
In large scale biological experiments, like high-throughput or high-content cellular screening, the amount and the complexity of images to be analyzed are steadily increasing. To handle and process these images, well defined image processing and analysis steps need to be performed by applying dedicated workflows. Multiple software tools have emerged with the aim to facilitate creation of such workflows by integrating existing methods, tools, and routines, and by adapting them to different applications and questions, as well as making them reusable and interchangeable. In this review, we describe workflow systems for the integration of microscopy image analysis techniques with focus on KNIME and Galaxy.